Inner wall filler as a singular and significant source of indoor radon pollution in heritage buildings: An exhalation method-based approach. (15th August 2021) - Frutos, Borja; Martín-Consuegra, Fernando; Alonso, Carmen; Perez, Gloria; Peón, Joaquín; Ruano-Ravina, Alberto; Barros, Juan M.; Santorun, Ana M.
Abstract: The presence of radon in buildings is a matter of growing concern in the industry. A further layer of complexity is present in heritage buildings, where sources of exhalation other than those observed in more modern conventional buildings may render diagnosis and intervention even more difficult. This study explored the high exhalation rates originating in the inner fillers in thick elements such as bearing walls and structural floors and vaults characterising historic construction. They were found to be close to the values observed in soils and one to two orders of magnitude greater (range: 32.5 mBq/m2·s to 149.7 mBq/m2·s) than found in the construction materials themselves, such as granite. The radon emitted into building interiors by those members exhibited more or less uniform concentration profiles on all storeys, irrespective of elevation and consequently distance form the soil. Further to the results delivered by an accumulative model, the only explanation for the empirical findings is that the inner filler in structural members sources a substantial fraction of the high exhalation rates. That would open a new exploratory pathway for remedies that should necessarily address all emissions, rather than deeming the soil as the sole or primary source of radon gas. The issue is broached in this article on the grounds of a case study of the Tower of Hercules at Corunna, Spain, a building dating from Roman times and presently used as a museum and monument open to the public. Graphical abstract: Image 1 Highlights: Significant sources of radon detected in walls in historic buildings . Tests on Roman building with 2.3 m thick walls and opus caementitium filler . Intense exhalation sourced from inner filler in ultra-thick walls . Inner filler exhalation favoured by joints between ashlars . Exhalation rates 1- to 2-fold higher in jointed surfaces .